THE INFLUENCE OF PERCEPTION, PROMOTION AND KNOWLEDGE ON THE DECISION TO BECOME A DEPOSIT CUSTOMER AT PT BPR BKK PURWOREJO (Perseroda) - Mutsanna, Ahmad Syarif (Politeknik Sawunggalih Aji, 2024)
The influence of perception, promotion, and knowledge aims to determine how much influence customers have in depositing their funds. The data used in this study are qualitative and quantitative. The methods used are interviews and observations. This study aims to determine the influence of perception, promotion, and knowledge on the decision to become a deposit customer at PT BPR BKK Purworejo (Perseroda) Bayan Branch. The population in this study were deposit customers at PT BPR BKK Purworejo (Perseroda) Bayan Branch with a sample size of 30 people. The instrument used in this study was a questionnaire on the decision to become a deposit customer that had previously been tested and had met the validity and reliability requirements, while for data analysis, multiple regression analysis was used. The results of this study indicate that the results of the t-test analysis on the perception variable showed a significant value greater than 0.05, namely 0.609> 0.05, did not have a significant effect on the decision to become a deposit customer. The results of the t-test on the promotion variable show a significant value greater than 0.05, namely 0.146> 0.05, which does not have a significant effect on the decision of deposit customers. The results of the t-test on the knowledge variable show a significant value less than 0.05, namely 0.012 <0.05, which has a significant effect on the decision to become a deposit customer. The results of the F-test analysis show that the F-test value is 3,565 with a significant amount of 0.028 less than 0.05, meaning that the perception, promotion and knowledge variables have a significant effect on the decision to become a deposit customer at PT BPR BKK Purworejo (Perseroda) Bayan Branch.